Foreign Aid: A Form of Dependency in Nepal - Gyawali, Gorkarna Pd. (Economic Journal of Development Issues, 2010)
The economic importance of foreign aid resides not only in the fact that it provides the resources for the national budget; rather, it also helps to bridge the gap between national savings and investment. Foreign aid helps to meet the gap between excess of imports in and exports of goods and services. But after the age of 1990s, it was gradually realized that the role and impact of foreign aid in Nepal has been less effective. It is publicly held that it has not brought about the economic and social development that it had promised. In Nepal, foreign aid has been widened gaps in economic opportunities between the rich and poor and also has increased the dependency of country to the developed nations. This paper, basically, discusses issues related to the role and impact of foreign aid to the development plan of Nepal as well as the composition and sectoral priorities of foreign aid in Nepal. There is a debate about the proper utilization of foreign aid in the developing country like Nepal and this article also examine the visions and ways of aid utilization for both donor and recipient countries. Key words: Foreign aid; Utilization; Nepal; Dependency Economic Journal of Development Issues Vol. 9 and 10 (2008 & 2009) Combined Issue Page: 34-43